2016
DOI: 10.1242/jeb.131375
|View full text |Cite
|
Sign up to set email alerts
|

Ambient CO2, fish behaviour and altered GABAergic neurotransmission: exploring the mechanism of CO2-altered behaviour by taking a hypercapnia dweller down to low CO2 levels

Abstract: Recent studies suggest that projected rises of aquatic CO 2 levels cause acid-base regulatory responses in fishes that lead to altered GABAergic neurotransmission and disrupted behaviour, threatening fitness and population survival. It is thought that changes in Cl − and HCO 3 − gradients across neural membranes interfere with the function of GABA-gated anion channels (GABA A receptors). So far, such alterations have been revealed experimentally by exposing species living in low-CO 2 environments, like many oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 54 publications
(77 reference statements)
0
29
0
Order By: Relevance
“…The GABA A R model does seem to fit with principles of basic neuroscience, but it must be validated with more than the use of gabazine and behavioural studies. Nilsson and Lefevre, 2016;Regan et al, 2016). However, only a few studies have measured these parameters in the blood plasma of fish exposed to OA-relevant conditions (i.e.…”
Section: Pharmacological Considerationsmentioning
confidence: 99%
“…The GABA A R model does seem to fit with principles of basic neuroscience, but it must be validated with more than the use of gabazine and behavioural studies. Nilsson and Lefevre, 2016;Regan et al, 2016). However, only a few studies have measured these parameters in the blood plasma of fish exposed to OA-relevant conditions (i.e.…”
Section: Pharmacological Considerationsmentioning
confidence: 99%
“…Tissues (heart, brain, liver, white muscle, kidney and lung) were quickly dissected (within 5 min), placed in micro-centrifuge tubes, frozen in liquid nitrogen and stored at −80°C for later measurements of pH i . Tissue was subsequently ground under liquid nitrogen and pH i was measured using the metabolic inhibitor tissue homogenate method; this technique has been validated (Baker et al, 2009b;Portner et al, 1990) and used in fish (Baker and Brauner, 2012;Baker et al, 2015;Brauner et al, 2004;Regan et al, 2016) and non-fish (Busk et al, 1997;Galli and Richards, 2012) studies. Plasma Na + , K + , Cl − and Ca 2+ were measured in embryos at 90% of incubation at each rearing condition using Stat Profile Prime (Nova Biomedical, Waltham, MA, USA).…”
Section: Blood Sampling Tissue Sampling and Ions Embryosmentioning
confidence: 99%
“…Recent studies have shown that ecologically important behavioral traits, such as activity and boldness, are affected by various emerging aquatic contaminants (Reyhanian et al, 2011;Brodin et al, 2013;Dzieweczynski et al, 2016) as well as other contaminants including inorganic mercury (Pereira et al, 2016), persistent organic pollutants (Vignet et al, 2015), and mining waste leachate (Lanctôt et al, 2016). Effects on boldness and activity have also been noted in response to ongoing large-scale changes in carbon dioxide (CO 2 ) concentrations in oceans and freshwaters (Munday et al, 2009(Munday et al, , 2010Welch et al, 2014;Regan et al, 2016). In other words, many laboratory assays imply that fish may change their activity and boldness in response to various environmental changes.…”
Section: Introductionmentioning
confidence: 99%